The Pedagogical Enhancement of Open Education: An Examination of Problem-Based Learning - Gurell, Seth; Kuo, Yu-Chun; Walker, Andrew (International Review of Research in Open and Distributed Learning, 2010)
Open education, as embodied in open educational resources (OER) and OpenCourseWare (OCW), has met and dealt with several key problems. The movement now has a critical mass of available content. Leveraging no small amount of funding and associated development, open education has the tools to collect, disseminate, and support the discovery of open materials. Now that the foundation for openness has been laid, practitioners are experimenting with new kinds of education and pedagogies associated with open content (Weller, 2009; di Savoia, 2009). Problem-based learning is one of many progressive pedagogies that might be combined with open education. This paper defines problem-based learning in the context of open education. Unique challenges are presented and discussed alongside possible solutions, realistic limitations, and calls for implementation in the future to test validity.